SPERMATOGENESIS FOLLOWING DISCONTINUATION OF CALCIUM CHANNEL BLOCKER AMLODIPINE IN RATS - Latif, Rabia; Aslam, Muhammad; Mehmood, Tariq (Journal of Ayub Medical College Abbottabad, 2009)
Background: The calcium channel blockers are commonly associated with male infertility. Long term administration of such drugs has been shown to suppress spermatogenesis. The present study was designed to determine the effects of cessation of calcium channel blocker (amlodipine) medication on spermatogenesis. Methods: The study was carried out in the Department of Physiology, in collaboration with Department of Pathology, Army Medical College, and National Institute of Health, Islamabad from April 2007 to March 2008. Thirty male rats were divided into two groups A and B each containing 15 rats. Group A rats were given distilled water (vehicle) whereas group B rats were given amlodipine by oral gavage for 50 days. After 50 days, amlodipine/distilled water was withdrawn. The rats were left for recovery to take place for another 50 days of drug withdrawal period. Testes were removed in all the rats and sectioned. The sections were stained with haematoxylin and eosin and examined microscopically. Results were analyzed using SPSS version 13. Results: Fifty days after drug withdrawal, there were statistically insignificant differences in mean tubular diameter and height of germinal epithelium between amlodipine treated and vehicle treated groups. Conclusion: Spermatogenesis in amlodipine treated rats does not differ significantly from spermatogenesis in vehicle treated rats after 50 days of drug withdrawal period. Keywords: Calcium channel blocker, CCB, amlodipine, male contraception, testicular histology, spermatogenesis, Dihydropyridine, DHP